Juvenile hormone resistance gene Methoprene-tolerant controls entry into metamorphosis in the beetle Tribolium castaneum - Konopova, Barbora (National Academy of Sciences, 2007)
Besides being a spectacular developmental process, metamorphosis is key to insect success. Entry into metamorphosis is controlled by juvenile hormone (JH). In larvae, JH prevents pupal and adult morphogenesis, thus keeping the insect in its immature state. How JH signals to preclude metamorphosis is poorly understood, and a JH receptor remains unknown. One candidate for the JH receptor role is the Methoprene-tolerant (Met) Per-Arnt-Sim (PAS) domain protein [also called Resistance to JH, Rst (1)JH], whose loss confers tolerance to JH and its mimic methoprene in the fruit fly Drosophila melanogaster. However, Met deficiency does not affect the larval–pupal transition, possibly because this process does not require JH absence in Drosophila. By contrast, the red flour beetle Tribolium castaneum is sensitive to developmental regulation by JH, thus making an ideal system to examine the role of Met in the antimetamorphic JH action. Here we show that impaired function of the Met ortholog TcMet renders Tribolium resistant to the effects of ectopic JH and, in a striking contrast to Drosophila, causes early-stage beetle larvae to undergo precocious metamorphosis. This is evident as TcMet-deficient larvae pupate prematurely or develop specific heterochronic phenotypes such as pupal-like cuticular structures, appendages, and compound eyes. Our results demonstrate that TcMet functions in JH response and provide the critical evidence that the putative JH receptor Met mediates the antimetamorphic effect of JH.